2021
DOI: 10.1111/ele.13930
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of key metabolites determine the global distribution of lichens

Abstract: In lichen symbioses, fungal secondary metabolites provide UV protection on which lichen algae such as trebouxiophycean green algae—the most prominent group of photobionts in lichen symbioses—sensitively depend. These metabolites differ in their UV absorbance capability and solvability, and thus vary in their propensity of being leached from the lichen body in humid and warm environments, with still unknown implications for the global distribution of lichens. In this study covering more than 10,000 lichenised f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…The symbiotic association, found in lichens, is a type of coevolution that allows these species to be distributed in a cosmopolitan pattern from polar to desert areas. Recent studies suggest that the production of secondary metabolites plays an important role in their environmental adaptation, and thus in their global distribution [ 102 ]. For instance, fumarprotocetraric acid from Cetraria islandica is related with the heavy metal tolerance of lichens due to its role in their reduction of metal ion absorption in the apoplast.…”
Section: Phytochemistrymentioning
confidence: 99%
“…The symbiotic association, found in lichens, is a type of coevolution that allows these species to be distributed in a cosmopolitan pattern from polar to desert areas. Recent studies suggest that the production of secondary metabolites plays an important role in their environmental adaptation, and thus in their global distribution [ 102 ]. For instance, fumarprotocetraric acid from Cetraria islandica is related with the heavy metal tolerance of lichens due to its role in their reduction of metal ion absorption in the apoplast.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Lichens are naturally occurring, stable microorganisms, and they are mutually beneficial organic complexes with a complex composition of fungal and chlorophyll organisms [1,2]. Mutualistic symbiosis is the biologically distinctive characteristic that allows lichens to be differentiated from other common plants [3]. Among the symbiotic microorganisms existing in lichens, ascomycetes are the pivotal symbiotic fungi that account for their fungi diversity.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that lichens can be readily encountered in nature, ranging from the North and South Poles to the equator, from mountains to plains, forests to deserts, and land to sea [5][6][7][8][9]. Due to their complex environmental living conditions, they display an outstanding capacity to produce numerous intriguing bioactive secondary metabolites to resist external habitat stresses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from lichen fossils indicated that the interactions between fungi and algae have existed for at least 400 million years (Lücking and Nelsen, 2018 ), and studies have shown that lichen occurs over 10% of the terrestrial surface, especially extreme and aggressive environmental conditions that are not conducive to individual survival, such as extreme cold Arctic and Antarctic regions (Lee et al, 2014 ), hot and arid deserts (Kranner et al, 2008 ), alpine areas with strong UV irradiation, and on rocks or non-fertile soils (de Vera et al, 2003 ; Seymour et al, 2005 ; Boustie et al, 2010 ; Nguyen et al, 2013 ). This tendency of lichens to tolerate the extreme environment can be correlated with the production of both a unique and diverse range of metabolites known as lichen substances (Schweiger et al, 2022 ). Fungi and algae co-evolved unique biosynthetic pathways and metabolic mechanisms to synthesize these complex metabolites over a long period of time.…”
Section: Introductionmentioning
confidence: 99%